Validitas Media Animasi Kartun Materi Siklus Air Kelas V Sekolah Dasar - Nadya Mira Velda; Dea Mustika (Civiliza Publishing, 2022)
The purpose of this study was to develop a learning media in the form of animated cartoons on the water cycle material for class V Elementary School. Cartoon animation learning media makes it easier for teachers and students to overcome problems during learning. This research method uses the ADDIE model development method. The ADDIE development model consists of five stages, namely: Analysis, Design, Development, Implementation, and Evaluation. However, the research is limited to: 1) the analysis stage consists of educator analysis, student analysis and learning material analysis. 2) the design stage consists of designing an animated cartoon in the form of powtoon and acemovi, 3) the development stage, namely realizing a learning media in the form of animated cartoons and compiling according to the needs that have been obtained at the analysis stage. The researcher also compiled a validation sheet that would be filled out by experts, totaling six expert validators including: two design experts, two material experts and two linguists. The results of this study indicate that the cartoon animation learning media meets the very valid criteria as evidenced by the acquisition of an average value of 92.90%.